2008
DOI: 10.1097/prs.0b013e3181882013
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-Infusion Local Anesthetic Pain Pump Use and Seroma Formation with Abdominal Procedures: Is There a Correlation?

Abstract: There was no correlation between increased rate of seroma formation and use of a continuous-infusion local anesthetic pain pump system in our patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The surgeon should be aware of the associated risk factors and potential complications following this popular procedure. Seroma, hematoma, wound dehiscence, and wound infection are common complications associated with abdominoplasty [12], with seroma as the most frequent complication with reported rates ranging from 3.0 to 37.3 % [5,8,[13][14][15][16][17][18][19][20]. The actual complication rate for cosmetic abdominoplasty, however, remains elusive because of the lack of large outcome studies.…”
Section: Introductionmentioning
confidence: 99%
“…The surgeon should be aware of the associated risk factors and potential complications following this popular procedure. Seroma, hematoma, wound dehiscence, and wound infection are common complications associated with abdominoplasty [12], with seroma as the most frequent complication with reported rates ranging from 3.0 to 37.3 % [5,8,[13][14][15][16][17][18][19][20]. The actual complication rate for cosmetic abdominoplasty, however, remains elusive because of the lack of large outcome studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, two studies based on the same patient material showed that the pain pump was not associated with an increased risk of postoperative infection [32] or seroma formation rate [33] in patients undergoing aesthetic and reconstructive abdominal procedures.…”
Section: Discussionmentioning
confidence: 98%
“…Upon reviewing the literature for similar cases, seromas were reported to be the most common encountered and serious complication following abdominal procedures in plastic and aesthetic surgeries. 5 However, it was only stated that they appear as an early complication for these types of procedures. It was also stated in literature that seromas can develop a fibrous pseudocapsule around them if they were not identified and treated immedietly.…”
Section: Discussionmentioning
confidence: 99%